ANALISIS TREN INTEGRASI TEKNOLOGI DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH: STUDI LITERATUR - M. Saddam Al Husein; Zila Razilu; Alfiah Fajriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The development of digital technology has become an important component in the implementation of the Merdeka Curriculum; however, studies that systematically map trends in technology integration within its implementation remain limited. This study aims to analyze trends in technology integration in the implementation of the Merdeka Curriculum in schools through a Systematic Literature Review (SLR) approach. The study reviewed scientific articles published between 2020 and 2025 that discussed the use of technology in teaching and learning at the primary and secondary education levels. Article searches were conducted through national and international databases using the keywords technology integration, digital learning, Merdeka Curriculum, e-learning, and blended learning. The article selection process followed the PRISMA procedure, including identification, screening, eligibility, and inclusion stages, resulting in 20 relevant articles for analysis. The findings indicate that technology integration in the implementation of the Merdeka Curriculum generally contributes positively to the quality of learning, particularly by enhancing student engagement and supporting more flexible, student-centered learning. The success of technology integration is influenced by teachers’ digital competence, students’ readiness, and support from the school environment. However, its implementation still faces challenges related to infrastructure readiness and digital literacy. These findings emphasize that the effective use of technology must be accompanied by appropriate pedagogical strategies to optimally support the implementation of the Merdeka Curriculum. Therefore, strengthening teachers’ digital competencies and developing innovative learning practices are necessary to support adaptive and effective 21st-century learning. ABSTRAK Perkembangan teknologi digital menjadi bagian penting dalam implementasi Kurikulum Merdeka, namun kajian yang secara sistematis memetakan tren integrasi teknologi dalam implementasinya masih terbatas. Penelitian ini bertujuan untuk menganalisis tren integrasi teknologi dalam implementasi Kurikulum Merdeka di sekolah melalui pendekatan Systematic Literature Review (SLR). Penelitian dilakukan dengan menelaah artikel ilmiah yang terbit pada rentang tahun 2020–2025 dan membahas penggunaan teknologi dalam pembelajaran pada jenjang pendidikan dasar dan menengah. Proses pencarian artikel dilakukan melalui basis data nasional dan internasional menggunakan kata kunci technology integration, digital learning, Kurikulum Merdeka, e-learning, dan blended learning. Seleksi artikel dilakukan melalui tahapan identifikasi, penyaringan, kelayakan, dan inklusi berdasarkan prosedur PRISMA sehingga diperoleh sebanyak 20 artikel yang relevan untuk dianalisis. Hasil penelitian menunjukkan bahwa integrasi teknologi dalam implementasi Kurikulum Merdeka secara umum memberikan kontribusi positif terhadap kualitas pembelajaran, terutama dalam meningkatkan keterlibatan peserta didik dan mendukung pembelajaran yang lebih fleksibel serta berpusat pada peserta didik. Keberhasilan integrasi teknologi dipengaruhi oleh kompetensi digital guru, kesiapan peserta didik, dan dukungan lingkungan sekolah. Namun, implementasinya masih menghadapi berbagai tantangan yang berkaitan dengan kesiapan infrastruktur dan literasi digital. Temuan ini menegaskan bahwa pemanfaatan teknologi perlu diimbangi dengan strategi pedagogik yang tepat agar dapat mendukung implementasi Kurikulum Merdeka secara optimal.. Oleh karena itu, diperlukan penguatan kompetensi digital guru dan pengembangan pembelajaran inovatif untuk mendukung pembelajaran abad ke-21 yang adaptif dan efektif.